The acute effect of match-play on hip range of motion and isometric strength in elite tennis players - Moreno-Pérez, Victor; Nakamura, Fabio Yuzo; Sánchez-Migallón, Violeta; Domínguez, Raul; Fernández-Elías, Valentín Emilio; Fernández-Fernández, Jaime; Pérez-López, Alberto; López-Samanes, Alvaro (PeerJ, 2019)
Background Groin injuries are some of the most common injuries tennis players suffer. Several factors (e.g., post-match decrease in hip adductor (ADD) strength) have been proposed as possible mechanisms for increasing the incidence of this type of injury. However, the risk factors of developing groin injuries after a tennis match have not yet been delineated. Objective The aim of this study was to determine the effect of tennis match-play on isometric ADD and abductor (ABD) strength and passive hip range of motion (ROM). Methods Twenty-six male tennis players (20.30 ± 4.98 years) took part in this study. Participants completed an evaluation of strength and flexibility hip measurements before and after a simulated tennis match. Dominant and non-dominant passive hip ROM, ADD and ABD isometric strength, and the ADD/ABD strength ratio were measured before and immediately post-match. A global positioning system (GPS) and a session rating of perceived exertion (RPE) were used to assess the locomotive demands and internal match load. Results Isometric dominant ADD strength (17.8%, p ≤ 0.01) and ADD/ABD strength ratio (11.6%, p = 0.04) were lower post-match compared to the pre-match values. No between-limbs differences were observed for isometric ADD strength, ABD strength, and passive hip ROM tests. RPE showed an expected increase between pre- vs. post-match (pre- vs. post-warming-up, 3.42 ± 2.08 vs. 5.62 ± 2.29, p < 0.01). In addition, a significant relationship between ADD strength and the volume of tennis practice per week was found, stablishing that tennis players with lower volume of training per week suffered a reduction in ADD strength in their dominant limb after match-play (r = 0.420, p = 0.04). Conclusion The assessment of ADD strength and the ADD/ABD strength ratio in the dominant limb may be considered a post-match tool that can be used to identify players who require rest and additional recovery strategies before competing again.
Keywords: Hip; njury prevention; ange of motion; ennis; trength; GPS